Investigation of the applied voltage influence on the ionizing radiation particles detecting by diamond detectors; Перспективы развития фундаментальных наук; Т. 1 : Физика - Okhotnikov V. V. Vitaly Vladimirovich (2017, 2017)
Заглавие с экрана